2021
DOI: 10.15441/ceem.21.066
|View full text |Cite
|
Sign up to set email alerts
|

Global prevalence of cardiopulmonary resuscitation training among the general public: a scoping review

Abstract: A scoping review was conducted to identify, map, and analyze international evidence from studies investigating the prevalence of community cardiopulmonary resuscitation (CPR) training. We searched major bibliographic databases and grey literature for original studies evaluating the prevalence of CPR training in the general population. Studies published from January 2000 to October 2020 were included without language or publication type restrictions. Seventy-three eligible papers reported a total of 61 populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 61 publications
(163 reference statements)
0
15
0
1
Order By: Relevance
“…Despite the efforts to enhance penetration of CPR training into the society [ 3 , 4 ], yet the opportunities to get trained in CPR are limited [ 5 , 6 ] and population coverage with resuscitation education remains low [ [7] , [8] , [9] ]. Layperson resuscitation training is less accessible for specific racial, ethnic and low socioeconomic status populations [ 3 , 10 , 11 ] and for people with disabilities [ 12 ].…”
mentioning
confidence: 99%
“…Despite the efforts to enhance penetration of CPR training into the society [ 3 , 4 ], yet the opportunities to get trained in CPR are limited [ 5 , 6 ] and population coverage with resuscitation education remains low [ [7] , [8] , [9] ]. Layperson resuscitation training is less accessible for specific racial, ethnic and low socioeconomic status populations [ 3 , 10 , 11 ] and for people with disabilities [ 12 ].…”
mentioning
confidence: 99%
“…A recently published systematic review and meta-analysis by Ng et al [2] corroborated the findings of the aforementioned scoping review [1]. In particular, based on the results of 17 studies, the pooled prevalence of ever been trained in CPR in the general global population was 39.6% (ranging from 3% to 65%), and significant variation was demonstrated for CPR training rates among continents and countries with different gross national income levels (43.6%, 40.1%, and 3.0% for high-, upper middle-, and lower middle-income levels, respectively) [2].…”
mentioning
confidence: 54%
“…A scoping review conducted by our research group [ 1 ] was the first study that investigated international evidence from population-based surveys reporting the prevalence of community resuscitation training. Based on 61 published studies conducted in 29 countries, the review showed the following: (1) a lack of data on community CPR training for most countries of the world, (2) a predominance of studies conducted in high-income countries compared to countries with low-income economies, and (3) considerable variation in reported CPR training rates (3%–79%) with a median global prevalence of CPR training amounting to 40% [ 1 ].…”
mentioning
confidence: 99%
“…This is similar to the results of Nie Shaozhou et al [7] In the United States, one in four people can perform CPR, this shows that there are still shortcomings in the popularization of AED in our province, and also reflects the urgency of PAD plan. Data show that the public penetration rate of AED education is 79% in the United States, 74% in Australia, 64% in Canada, [8] 61% in the United Kingdom, [9] 31.1% in West Africa, [10] whereas only 1% of the Chinese public qualified for AED training for OHCA. [11] Therefore, to enhance knowledge and skills training, the Global Resuscitation Alliance proposes CPR and AED training in schools and communities to improve OHCA survival rates, as emphasized in the "Saving Lives of Children" declaration, which has substantial evidence that school-age children can play a critical role in improving OHCA survival rates.…”
Section: Discussionmentioning
confidence: 99%